Bio-active constituents from Schisandra grandiflora: Isolation, semi-synthesis and evaluation of their anticancer activities. (October 2021) - Amujuri, Devi; Siva, Bandi; Bharathi, K.; Poornima, B.; Supriya, B.; Ummanni, Ramesh; Babu, K. Suresh
Graphical abstract: Highlights: Two new widdarane-sesquiterpenes were isolated from the fruits of Schisandra grandiflora . The structures of new compounds were characterized by NMR and Mass spectral techniques. A series of derivatives from a major compound, gomosin N (4 ) were prepared by esterification with different acids. Among the tested derivatives, 8a and 8h were manifested promising activity against MCF-7 and MIA PaCa cell lines. Abstract: In continuation of our efforts in the exploration of Indian flora and development of new natural product-based therapeutics, bio-activity directed investigation of Schisandra grandiflora led to the isolation of two new widdarane-sesquiterpenes (1 and 2 ) along with four known compounds (3 - 8 ). Further, a series of derivatives from a major compound, gomosin N (4 ) were prepared by ring-opening of methylenedioxy group using Pb(OAc)4 and followed by esterification with different acids. The structures of isolates and synthesized derivatives were confirmed by interpretation of spectral studies (NMR and Mass) and screened for their potentials against a panel of cancer cell lines. Among the tested derivatives, 8a and 8h were manifested promising activity than gomisin N (3 ) against MCF-7 and MIA PaCa cell lines.